STABILITAS SERUM LYOPHILIZED HOMEMADE REKONSTITUSI TERHADAP KADAR KREATININ DAN BLOOD UREA NITROGEN (BUN) YANG DISIMPAN DALAM FREEZER - Anggie Banowati Wibiseno; Anik Handayati; Syamsul Arifin (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Quality control is an activity that can improve the quality of the laboratory which is carried out byconducting an examination using a control serum. Homemade lyophilized serum is an alternative control serumthat is relatively inexpensive and easy to obtain than commercial control serum. This study aimed to determinethe stability of reconstituted homemade lyophilized control serum stored for 8 weeks at a temperature of (-2)ºCto(-4)ºCand(-20)ºConcreatinineandBUNlevels. This research was conducted at the Clinical Laboratory of Poltekkes Kemenkes Surabaya in March-May 2022 with the type of experimental research and a one group pretest-posttest design. The reconstitutedhomemade lyophilized serum was stored at (-2)ºC to (-4)ºC and (-20)ºC, the serum was checked once a week for8weeks. The results of homemade lyophilized serum creatinine and BUN levels after reconstitution stored at (-2)ºC to (-4)ºC and (-20)ºC were not out of the control limit ±2SD so they could be declared stable with a CVcreatinine value 4-6% and BUN 7-8%. Based on the regression test analysis, it is known that storage time has aneffect of 51.3% on serumcreatinine levels stored at (-2)ºC to (-4)ºC and has an effect of 79.3% on serumcreatinine levels stored at (-20)ºC. Storage time has an effect of 76% on serum BUN levels stored at (-2)ºC to (-4)ºCand75.1%effectonserumcreatininelevels storedat(-20)ºC.